Psalm 89 and Daniel 7 - Venter, Pieter M. (Old Testament Essays, 2004)
Mosca suggested that the Ancient of Days in Daniel 7 can be related to the hymn in Psalm 89:2-3, 6-19. This paper investigates this theory by analysing the construction of the whole of Psalm 89. It draws the conclusion that not only the hymn, but also the oracle in Psalm 89:20- 38 as well as the complaint in Psalm 89:39-52 functioned as intertext in the composition of Daniel's heavenly vision in Daniel 7.
free